Effect of lateral structure parameters of SiGe HBTs on synthesized active inductors - 赵彦晓 张万荣 黄鑫 谢红云 金冬月 付强 (Chinese physics B, 2016)
The effect of lateral structure parameters of transistors including emitter width, emitter length, and emitter stripe number on the performance parameters of the active inductor （AI）, such as the effective inductance Ls, quality factor Q, and self-resonant frequency too is analyzed based on 0.35%tm SiGe BiCMOS process. The simulation results show that for AI operated under fixed current density Jc, the HBT lateral structure parameters have significant effect on Ls but little influence on Q and 090, and the larger Ls can be realized by the narrow, short emitter stripe and few emitter stripes of SiGe HBTs. On the other hand, for AI with fixed HBT size, smaller Jc is beneficial for AI to obtain larger Ls, but with a cost of smaller Q and 090. In addition, under the fixed collector current Ic, the larger the size of HBT is, the larger Ls becomes, but the smaller Q and ab become. The obtained results provide a reference for selecting geometry of transistors and operational condition in the design of active inductors.